Monitoring Carbonation Levels in Beverage Production Using X-Bar/R-Charts and Tabular CUSUM: A Statistical Process Control Study at Seven-Up Bottling Company, Kaduna, Nigeria - Chinedu Samuel Onyedika (Darul Yasin Al Sys, 2026)
Carbonation is a defining sensory attribute of carbonated soft drinks and a critical determinant of product quality because carbon dioxide (CO₂) volume directly influences taste, perceived freshness, mouthfeel, and consumer acceptability. Deviations from specified carbonation levels can result in under-carbonated beverages that taste flat and stale or over-carbonated products characterized by excessive foaming, premature cap ejection, and potential bottle-integrity failures. Maintaining consistent CO₂ volume is particularly challenging in high-capacity bottling operations such as Seven-Up Bottling Company, Kaduna, which produces up to 800,000 bottles daily across multiple product types and bottle sizes. Carbonation levels may fluctuate because of variations in beverage temperature, syrup concentration, filling pressure, and machine calibration across production shifts. This study aims to evaluate the statistical stability of the carbonation process and distinguish common-cause variation from assignable-cause variation in CO₂ volume. A dataset comprising 30 production subgroups, generated through the facility’s 30-minute gas-volume monitoring procedure, was analyzed using Statistical Process Control techniques. The X-bar and R-chart combination was applied to assess process central tendency and dispersion, while the Cumulative Sum chart was used to detect small and persistent shifts that might not be readily identified through conventional control charts. The combined application of these methods provides a systematic framework for identifying abnormal carbonation patterns, supporting timely corrective action, and strengthening process-control decisions. This study contributes the first documented Statistical Process Control analysis of carbonation quality at the Kaduna facility and offers a practical basis for improving product consistency, reducing quality failures, and enhancing consumer acceptability in large-scale beverage production.